COMPREHENSIVE ASSESSMENT GUIDELINES FOR QUALITY ASSURANCEIN THE EUROPEAN HIGHER EDUCATION AREA - Costa, Rebeca Soler (European Scientific Journal, ESJ, 2014)
Roughly speaking, the scientific literature seems to associate assessment with the score a student gets. However, assessment goes beyond that and is only real if students acquire learning. This can be achieved with feedback (formative evaluation). In the 2010- 2011 academic year we created a space in "moodle" for students to participate actively in solving activities and case analysis for the subject "The school as an educational space" in the Degree in Teaching for Primary Education in the Faculty of Education (University of Zaragoza). This space allows students to acquire a complementary learning on the basis of self-regulation and according to the feedback they receive. It is also important to consider teaching styles and learning strategies. For this reason, along this paper we will examine how assessment with new tools and techniques can assure quality in the comprehensive assessment through the establishment of some guidelines and didactic strategies. To perform the evaluation of this course, students developed an e-portfolio, uploading it in "moodle" so the rest of students could observe the work other students had made, thus increasing their individual requirement level. The key issue was the authenticity, relevancy and appropriateness of the activities we raised. Undoubtedly, the development of the teachinglearning processes and their assessment can be highly enhanced by the introduction of appropriate tools in the classroom to encourage active student participation and their learning feedback.